Reinforcing pore structure and ITZ of foam concrete enabled by DNA self-assembled CNTs networks - Tianye Luo; Xingu Zhong; Yi Zhou; Xinke Zhang; Qianxi Li; Chao Zhao; Xiong Peng; Hongxin Sun (Case Studies in Construction Materials)
In this study, CNTs networks were formed on the foam and quartz sand based on the self-assembly of deoxyribonucleic acid (DNA), which propose two organic-inorganic hybrid materials (CNTs-sand and CNTs-foam) for reinforcing foam concrete. DNA can not only disperse CNTs by π-π stacking but also form ionic-hydrogen bond with KOH modified quartz sand. On the other hand, a three-phase foam stabilized by DNA/CNTs was prepared. The test results of mechanical properties indicated that the compressive, splitting tensile and bending strength are impressively increased by 2 times, 3 times and 2 times compared to control group. CNTs-foam and CNTs-sand did not promote the hydration reaction, according to XRD and TG test results. The enhancement of mechanical properties is predominantly driven by the optimization of pore structure and interfacial transition zone (ITZ), as evidenced by SEM, X-CT and nanoindentation. This paper provides an innovative strategy for CNTs dispersion in foam concrete and contributes to designing high-performance foam concrete.